Document images forgery localization using a two‐stream network. Issue 8 (29th December 2021) - Xu, Wenbo; Luo, Junwei; Zhu, Chuntao; Lu, Wei; Zeng, Jinhua; Shi, Shaopei; Lin, Cong
Abstract: Document images often contain essential and sensitive information. With image editing software, one can easily manipulate the semantic meaning of the document image by copy‐move, splicing, and removal, which causes many security issues. Hence, the document image forgery detection and localization are of great significance. In this paper, a novel two‐stream network is proposed to detect and locate the forgery regions of document images. One stream captures forgery traces from the spatial information, including unnatural boundaries, contrast/brightness inconsistencies, and blurring. The other stream eliminates the image semantics by six residual filters, then capture the anomalous features between neighboring pixels introduced by upsampling, downsamping, and inpainting. Finally, the discriminant network is introduced to deeply fuse features from the two streams, and discriminates whether each image patch is forged or not using global average pooling and fully connected layer. Extensive experimental results on our constructed document image data set and the Security AI Challenger Program data set demonstrate the proposed two‐stream network outperforms state‐of‐the‐art methods. This proposed two‐stream network is also better than each single stream, and is robust to some common forgery postprocessing operations.